Fluid-Structure Interaction Simulation of Left Ventricular Blood Flow During the Systolic and Diastolic Phases - Moghaddaszde Kermani, Ahmad; Oshkai, Peter; Suleman, Afzal (CMBES Proceedings, 2009)
No Abstract